2013
DOI: 10.1038/srep02146
|View full text |Cite
|
Sign up to set email alerts
|

High levels of reactive oxygen species in gold nanoparticle-targeted cancer cells following femtosecond pulse irradiation

Abstract: Cancer cells could be locally damaged using specifically targeted gold nanoparticles and laser pulse irradiation, while maintaining minimum damage to nearby, particle-free tissue. Here, we show that in addition to the immediate photothermal cell damage, high concentrations of reactive oxygen species (ROS) are formed within the irradiated cells. Burkitt lymphoma B cells and epithelial breast cancer cells were targeted by antibody-coated gold nanospheres and irradiated by a few resonant femtosecond pulses, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 52 publications
(66 reference statements)
2
83
0
3
Order By: Relevance
“…We also demonstrate time-dependent cleavage of PARP, caspase 8, caspase 9 and caspase 3 at 30 μM in SUDHL-4 cells, at concentrations that have been shown to induce apoptosis (Figure 7). These data provide further evidence that AuNPs induced apoptosis is ROS and caspase-dependent, and may proceed by both intrinsic and extrinsic pathways [44]- [46]. …”
Section: Aunps Induces Parp and Caspase Cleavagesupporting
confidence: 58%
See 1 more Smart Citation
“…We also demonstrate time-dependent cleavage of PARP, caspase 8, caspase 9 and caspase 3 at 30 μM in SUDHL-4 cells, at concentrations that have been shown to induce apoptosis (Figure 7). These data provide further evidence that AuNPs induced apoptosis is ROS and caspase-dependent, and may proceed by both intrinsic and extrinsic pathways [44]- [46]. …”
Section: Aunps Induces Parp and Caspase Cleavagesupporting
confidence: 58%
“…We found that AuNPs resulted in significant (p < 0.05) dose-dependent apoptosis in SUDHL-4 at 48 h. The AC50 (defined herein as that concentration that achieved 50% apoptosis) was 30 μM for SUDHL-4 at 48 h [44]. To determine if apoptosis was related to ROS, we co-incubated cells with the anti-oxidant NAC.…”
Section: Aunps Induces Nac-reversible Caspase-dependent Apoptosis Inmentioning
confidence: 99%
“…Lastly, the formation of a PC can increase the safety of NPs by inhibiting the generation of radical oxygen species (ROS), by which several compounds exert their cytotoxic activity [121]. Nanoparticle toxicity can be related to the formation of ROS when the particles are composed of materials with semiconductor features [122,123]. In this context, ZnO NPs are again an example of this phenomenon because their pristine surface is a natural trigger of ROS, but the formation of a PC on their surface inhibits this phenomenon [113].…”
Section: Toxicological Implication Of the Pcmentioning
confidence: 99%
“…Apart from the heat produced by their plasmonic oscillations, there are some studies that suggest that there are other processes involved, like the apparition of more unpredictable reactive oxygen species (ROS) [8,12,13] as a result of the interaction of the nanomaterials with the incoming irradiation. ROS are highly reactive radicals (e.g.…”
Section: You Cannot Hit What You Cannot See: Understanding Pttmentioning
confidence: 99%
“…If raised higher than basal levels, ROS are able to disrupt biological functions by altering proteins, biological membranes and nucleic acids, and thus induce off-target cell death in an uncontrolled manner [12]. ROS levels can increase during heat generation and PTT [12,13], arising in unpredictable outcomes that may undermine the accuracy offered by this therapeutic approach. Minai and coworkers were amongst the first to publish a thorough study of the processes that induce ROS during PTT [13].…”
Section: You Cannot Hit What You Cannot See: Understanding Pttmentioning
confidence: 99%